(untitled) - Alfonso, Anthony (Tokyo, 1974)
Contents: Many students have made use of simpler grammars in their efforts to learn the language, and as a result they have never really grasped the total structure of Japanese. The solution to their problems will be found in these materials, and a number of people have expressed regret that these language patterns were not avaiable when they first studied Japanese
Keywords: Japanese language,Tiếng Nhật; Syntax,Cú pháp